Językowo-kulturowy obraz wsi i jej mieszkańców utrwalony w wiejskich toponimach (na przykładzie gminy Wręczyca Wielka w powiecie kłobuckim) - JELONEK, TOMASZ (Stylistyka, 2024)
This article is devoted to reconstruction of the linguistic-cultural picture of country villages and their inhabitants, which emerges from informal toponyms. The problem that is considered by the author is very important in the context of progressive changes of rural areas, widespread globalization processes and intergenerational exchange. The present study includes over 60 names of parts of villages, which were collected during the geographical exploration from 2022 to 2023 in the area of Wręczyca Wielka Commune situated next to Kłobuck in the north of Silesian Province. In the analysis of this onimic material, different kinds of ethnographic data, e.g. stories and legends, were used. The first part of the article is devoted to the specificity of the collected toponyms, basic methodological solutions and studies connected with the issue in question. In the second part – on the strength of language material analysis and the so-called co-linguistic data – it could be claimed that the picture of a country village as written down in the proper names reflects the environmental and cultural specificity of the region, e.g. little diversified configuration of the area, large scale forestation or value of life in the land. Creators of the names are also distinguished by their specific reception of the non-verbal reality which is mostly perceived by their sense of sight. Furthermore, the anthropocentric point of view and remembering the past very often accompany inhabitants of villages during nomination acts. They also take care of simplicity and practicality of components of this informal toponimic system.